Analisis Program Corporate Social Responsibility PT. X Regional Jawa Barat - Felicetiani Safrida; Riza Hernawati (Bandung Conference Series: Public Relations, 2021)
Abstract. Corporate Social Responsibility is a company obligation that must be carried out as a form of responsibility to the community. In addition, this activity is part of a business strategy in which there is a form of company concern for improving welfare. CSR can be done through various sectors, one of which is education. With the Covid-19 pandemic, learning activities have been hampered. Therefore, PT. West Java Regional X carries out CSR activities in the field of education through the "Merdeka Belajar" program by distributing starter packs and free quota to students. This program collaborates with the West Java Provincial Government. This research was conducted to determine the stages of Telkomsel West Java in determining the segmentation of quota recipients, and the stages of the “Merdeka Belajar” Program. In addition, this study aims to determine the reasons for Telkomsel West Java to partner with the West Java Provincial Government, as well as the reasons for Telkomsel West Java to carry out the CSR program "Merdeka Belajar”. Researchers used qualitative research methods with a case study approach. With observation data collection techniques, interviews, documents, and literature study. The results of this study explain the stages of Telkomsel in determining the segmentation of recipients through coordination between divisions at the head office and coordination of distribution segmentation strategies at the regional level. Then the stages of the CSR program "Merdeka Belajar" from the ideation stage of the head office to the implementation at the regional level by carrying out the stages of launching, distribution to aftersales and evaluation. In addition, in this study, it was found that the reason for the West Java Regional Telkomsel to collaborate with the West Java Provincial Government is to facilitate the bureaucracy and obtain data on aid recipients, and the reason for conducting CSR "Merdea Belajar" is to contribute to meeting the needs of students doing distance learning. Abstrak. Corporate Social Responsibility adalah kewajiban perusahaan yang harus dilakukan sebagai bentuk tanggung jawab kepada masyarakat. Di samping itu, kegiatan ini merupakan bagian dari strategi bisnis yang di dalamnya terdapat wujud kepedulian perusahaan untuk meningkatkan kesejahteraan. CSR dapat dilakukan melalui berbagai sektor, salah satunya adalah pendidikan. Dengan adanya pandemic Covid-19, kegiatan pembelajaran menjadi terhambat. Maka dari itu, PT. X Regional Jawa Barat melakukan kegiatan CSR di bidang pendidikan melalui program “Merdeka Belajar” dengan membagikan kartu perdana dan kuota gratis untuk para pelajar. Program ini bekerja sama dengan Pemerintah Provinsi Jawa Barat. Penelitian ini dilakukan untuk mengetahui tahap Telkomsel Jawa Barat menentukan segmentasi penerima kuota, tahapan kegiatan Program “Merdeka Belajar”. Selain itu penelitian ini ditujukan untuk mengetahui alasan Telkomsel Jawa Barat bermitra dengan Pemerintah Provinsi Jawa Barat, serta alasan Telkomsel Jawa Barat melakukan program CSR “Merdeka Belajar”. Peneliti menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Dengan teknik pengumpulan data observasi, wawancara, dokumen, dan studi kepustakaan. Hasil penelitian ini menjelaskan tahapan Telkomsel menentukan segmentasi penerima melalui koordinasi antar divisi di kantor pusat dan koordinasi strategi segmentasi distribusi di tingkat regional. Kemudian tahapan program CSR “Merdeka Belajar” dari tahap ideation kantor pusat hingga pelaksananya di tingkat regional dengan melakukan tahap launching, distribusi hingga aftersales dan evaluasi. Selain itu, pada penelitian ini ditemukan alasan Telkomsel Regional Jabar melakukan kerja sama dengan Pemprov Jabar yakni untuk mempermudah birokrasi dan mendapat data penerima bantuan, serta alasan melakukan CSR “Merdeka Belajar” adalah untuk turut berkontribusi memenuhi kebutuhan siswa melakukan pembelajaran jarak jauh.